2018
DOI: 10.1103/physrevapplied.9.024032
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Domain-Wall Surface Tension by Deflating or Inflating a Magnetic Bubble

Abstract: The surface energy of a magnetic Domain Wall (DW) strongly affects its static and dynamic behaviours. However, this effect was seldom directly observed and many related phenomena have not been well understood. Moreover, a reliable method to quantify the DW surface energy is still missing. Here, we report a series of experiments in which the DW surface energy becomes a dominant parameter. We observed that a semicircular magnetic domain bubble could spontaneously collapse under the Laplace pressure induced by DW… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 39 publications
4
46
0
Order By: Relevance
“…Jm     , which is in very good agreement with previous studies [37,43]. Finally, by considering 0 depin H  =16 mT, a typical gradient of δ~∆, the experimental values…”
supporting
confidence: 91%
“…Jm     , which is in very good agreement with previous studies [37,43]. Finally, by considering 0 depin H  =16 mT, a typical gradient of δ~∆, the experimental values…”
supporting
confidence: 91%
“…3b, c) indicate that domain contraction is significantly faster than domain expansion. We attribute this asymmetry to the tendency of the reversed domain to shrink in order to reduce the DW surface tension 37,38 . The latter is proportional to the DW length and can thus significantly offset the balance of SOT, pinning potential, and demagnetizing field.…”
Section: Resultsmentioning
confidence: 99%
“…X. Zhang et al . reported that the DW surface tension with regard to the iDMI influenced the static and dynamic DW behavior 39 . The DW surface tension can also be considerable to affect the asymmetrical semi-circular DW expansion at the junction.…”
Section: Resultsmentioning
confidence: 99%